Leadless pacemaker implantation: A feasible and reasonable option in transcatheter heart valve replacement patients. Issue 5 (18th March 2019) - Moore, Sarah K. L.; Chau, Katherine H.; Chaudhary, Salma; Rubin, Geoffrey; Bayne, Joseph; Avula, Uma Mahesh R.; Wang, Daniel Y.; Sorbera, Carmine; Dizon, Jose; Biviano, Angelo; Waase, Marc; Iyer, Vivek; et al.
Abstract: Background: Leadless pacemakers (LPMs) have been shown to have lower postoperative complications than traditional permanent pacemakers but there have been no studies on the outcomes of LPMs in patients with transcatheter heart valve replacements (THVRs). This study determined outcomes of LPMs compared to transvenous single‐chamber pacemakers (SCPs) post‐THVR. Methods: This is a retrospective single‐center study including 10 patients who received LPMs post‐THVR between February 2017 and August 2018 and a comparison group of 23 patients who received SCP post‐THVR between July 2008 and August 2018. LPM or SCP was implanted at the discretion of electrophysiologists for atrial fibrillation with slow ventricular response or sinus node dysfunction with need for single‐chamber pacing only. Results: LPMs were associated with decreased tricuspid regurgitation ( P  = 0.04) and decreased blood loss during implantation (7.5 ± 2.5 cc for LPMs vs 16.8 ± 3.2 cc for SCPs, P  = 0.03). Five LPM patients had devices positioned in the right ventricular septum as seen on transthoracic echocardiogram. Frequency of ventricular pacing was similar between LPM and SCP groups. In the LPM group, one case was complicated by a pseudoaneurysm and one death was due to noncardiac causes. There was one pneumothorax and one pocket infection in the SCP group. Conclusions: In this small retrospective study, LPMs were feasible post‐THVR and found to perform as well as SCPs, had less intraprocedural blood loss, and were associated with less tricuspid regurgitation. Further, larger studies are required to follow longer‐term outcomes and complications.